The effect of frailty should be considered in the management plan of older people with Type 2 diabetes. (March 2016) - Abdelhafiz, Ahmed H; Koay, Luan; Sinclair, Alan J
The prevalence of diabetes is increasing especially in older age due to increased life expectancy. In old age, diabetes is associated with high comorbidity burden and increased prevalence of geriatric syndromes including frailty in addition to micro- and macro-vascular complications. The emergence of frailty may change the natural history of Type 2 diabetes from a progressive to a regressive course with increased risk of hypoglycemia. This may result in normalization of blood glucose levels and lead to a state of burnt-out diabetes in frail older people with significant weight loss. Although guidelines suggest relaxed glycemic control in frail elderly with diabetes, complete withdrawal of hypoglycemic medications may be necessary in these frail populations to reduce the risk of hypoglycemia. Lay abstract: Diabetes is a common disease especially in older people. Aging is associated with reduced appetite and reduced food intake due to lack of exercise and diminished energy consumption. In certain individuals this may be significant leading to weight loss, malnutrition and the development of frailty. As a result the doses of diabetes medications may be too strong for this frail population especially if they have organ dysfunction reducing medication clearance and increasing the risk of low blood glucose level events. Therefore, reduction or complete withdrawal of diabetes medications may be considered in this frail group.